Location of Balanced Chromosome-Translocation Breakpoints by Long-Read Sequencing on the Oxford Nanopore Platform - Hu, Liang; Liang, Fan; Cheng, Dehua; Zhang, Zhiyuan; Yu, Guoliang; Zha, Jianjun; Wang, Yang; Xia, Qi; Yuan, Daoli; Tan, Yueqiu; Wang, Depeng; Liang, Yu; et al. (Frontiers in Genetics, 2020)
Structural variants (SVs) in genomes, including translocations, inversions, insertions, deletions, and duplications, are difficult to detect reliably by traditional genomics technologies. In particular, balanced translocations and inversions cannot be detected with microarrays since they do not alter chromosome copy numbers; they cannot be reliably detected by short-read sequencing either, since many breakpoints are located within repetitive regions of the genome that are unmappable by short reads. The precise localization of breakpoints is important for studying genetic causes in patients carrying balanced translocations or inversions. Long-read sequencing techniques, may detect these SVs in a more direct, efficient, and accurate manner. We performed whole-genome, long-read sequencing on an Oxford Nanopore GridION sequencer to detect breakpoints in6 carriers of balanced translocations and one inversion carrier, where SVs were initially detected by karyotyping at the chromosome level. The results showed that all balanced translocations were detected with 10 coverage and were consistent with the karyotyping results. Polymerase chain reaction (PCR) and Sanger sequencing experiments confirmed 8 of the 14 breakpoints at single-base resolution, yet other breakpoints were not refined to single-base resolution due to their localization in highly repetitive regions or pericentromeric regions, or the possible presence of local deletions/duplications. Long-read, whole-genome sequencing is an ideal tool for the precise localization of most translocation breakpoints and may provide haplotype information on breakpoint-linked single-nucleotide polymorphisms, which may be widely applied in SV detection, therapeutic monitoring, assisted reproduction technology, and preimplantation genetic diagnosis.